2023
DOI: 10.1515/med-2023-0629
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism by which the Notch signaling pathway regulates autophagy in a rat model of pulmonary fibrosis in pigeon breeder’s lung

Abstract: This study investigated the molecular mechanisms underlying the involvement of the Notch signaling pathway and autophagy in the development of pulmonary fibrosis in pigeon breeder’s lung (PBL). Rats were divided into control (Ctrl), PBL model (M), M + D (Notch signaling inhibition), M + W (autophagy inhibition), and M + R (autophagy induction) groups. Lyophilized protein powder from pigeon shedding materials was used as an allergen to construct a fibrotic PBL rat model. The mechanism by which Notch signaling r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…We successfully established an animal model of fibrotic HP by using pigeon exfoliates collected from the pigeon house of Xinjiang Xintou Pigeon Leaf Co., Ltd, in Kashgar, Xinjiang. 18 In this study, we divided the 18 PBL rats into the M group and the M+DAPT group and found that DAPT intervention greatly reduced the severity of inflammatory cell infiltration and fibrosis while preventing definitive granuloma formation. In the control group, pulmonary alveoli, bronchioles and blood vessels were normal, and no changes in inflammation or fibrosis were observed.…”
Section: Discussionmentioning
confidence: 97%
“…We successfully established an animal model of fibrotic HP by using pigeon exfoliates collected from the pigeon house of Xinjiang Xintou Pigeon Leaf Co., Ltd, in Kashgar, Xinjiang. 18 In this study, we divided the 18 PBL rats into the M group and the M+DAPT group and found that DAPT intervention greatly reduced the severity of inflammatory cell infiltration and fibrosis while preventing definitive granuloma formation. In the control group, pulmonary alveoli, bronchioles and blood vessels were normal, and no changes in inflammation or fibrosis were observed.…”
Section: Discussionmentioning
confidence: 97%